A new method for characterization of gate overlap capacitances and effective channel size in MOSFETs. (September 2019) - Tomaszewski, Daniel; Głuszko, Grzegorz; Kucharski, Krzysztof; Malesińska, Jolanta
Abstract: Methods for characterization of MOSFET gate overlap capacitances are briefly discussed. Considerations of their shortcomings due to the neglected shortening and/or narrowing of the MOSFET channel in relation to its drawn size have led to development of a new method for a simultaneous extraction of the gate overlap capacitances and of the channel width and length variations. The approach is presented and illustrated using experimental data obtained by C-V measurements of the MOSFETs in a CMOS test structure. The characterization results are compared with the parameters obtained via I-V measurements of the corresponding devices.